Dufour and Soret Effects on Unsteady MHD Free Convection and Mass Transfer Fluid Flow Through a Porous Medium in a Rotating System - Islam, Nazmul; Alam, Md. Mahmud (Bangladesh Journal of Scientific and Industrial Research, 2008)
The numerical studies are performed to examine the unsteady MHD free convection and mass transfer flow through a porous medium with thermal diffusion and diffusion thermo past an infinite vertical porous plate in a rotating system. Method of superposition is used as a main tool for numerical solution. The study is mainly based on the similarity approach. Impulsively started plate moving in its own plane is considered. Similarity equations of the corresponding momentum, energy and concentration equations are derived by introducing a time dependent length scale which infact plays the role of a similarity parameter. The velocity component is taken to be inversely proportional to this parameter. The effects on the velocity, temperature, concentration, local skin-friction coefficients, Nusselt number and the Sherwood number of the various important parameters entering into the problem separately are discussed with the help of graphs and tables. Key words: Numerical studies, Magnetohydronamics, Dufour, Soret, Rotating system DOI: 10.3329/bjsir.v43i2.959 Bangladesh J. Sci. Ind. Res. 43(2), 159-172, 2008